Knowledge Exchange and Power Dynamics in Academic Communities: A Sociological Examination of Collaborative Research Networks - Tuerah, Paulus Robert; Karamoy, Claudya; Ante, Lady D; Samahati, Susan Stefania; Silow, Susanti; Sumual, Tinneke Evie Meggy (Labor Program Studi Pendidikan Sosiologi, 2023)
This study aims to analyze knowledge-sharing patterns within collaborative research networks in higher education institutions, focusing on sociological aspects. The research employs a qualitative methodology through a systematic literature review, examining scientific articles published between 2019-2024. The analysis reveals three key findings: First, there is a significant transformation in communication patterns towards a more horizontal model, facilitated by digital platforms and changing academic hierarchies. Second, social capital plays a crucial role in knowledge-sharing effectiveness, with strong networks and trust relationships contributing to enhanced research collaboration. Third, institutional factors significantly influence collaboration dynamics, including organizational policies, digital infrastructure, and resource allocation. The results demonstrate that while digital transformation has democratized research collaboration, social and institutional factors continue to shape knowledge-sharing practices. The study identifies gaps in existing collaborative frameworks and recommends developing an integrated approach that addresses technological, social, and institutional dimensions. This framework aims to foster more inclusive and productive research networks in higher education. The findings contribute to understanding the complex interplay between digital transformation, social dynamics, and institutional structures in academic collaboration. The study suggests practical implications for higher education institutions seeking to enhance their collaborative research capabilities and provides directions for future research in this evolving field.